Bridging Citizen Science and Expert Surveys in urban biodiversity monitoring: Insights from insect diversity in Macao - Kaiyun Zheng; Mark K. L. Wong; Toby Tsang; Chi Man Leong (Biodiversity Data Journal)
Urban ecosystems present unique challenges for biodiversity monitoring, demanding efficient methods to document species diversity in rapidly changing environments. This study quantifies insect diversity in Macao SAR — a hyper-urbanised region — by integrating data on 1,339 species documented in expert-led surveys and 1,012 species recorded in citizen-science observations between 2019 and 2023. Striking divergence emerged between the expert and citizen-science datasets: only 462 species (33.5% of total diversity) were detected by both groups, with experts documenting 877 unique taxa often requiring specialised collection or morphological analysis, while citizen scientists contributed 550 distinctive species through spatially explicit, image-based records. Together, these approaches achieved 96.59% estimated species coverage within five years, demonstrating that combining community-driven data with expert methods accelerates comprehensive biodiversity documentation. Citizen-science platforms played a pivotal role by providing high-resolution geotagged imagery which enabled experts to validate records and resolve taxonomic ambiguities. Meanwhile, expert surveys detected cryptic taxa overlooked by citizen scientists. The rapid species coverage achieved through this synergy highlights the transformative potential of integrated frameworks. By mobilizing the scalability of citizen science to fill spatial and taxonomic gaps, while leveraging expert precision to ensure rigour, urban biodiversity monitoring can adapt to the rapid pace of ecological change. These findings advocate for collaborative strategies that harness public participation and scientific validation to optimise conservation efforts in data-deficient and highly-stressed ecosystems.